Renal hypouricemia caused by novel compound heterozygous mutations in the SLC22A12 gene: a case report with literature review - Zhaowei Zhou; Lidan Ma; Juan Zhou; Zhijian Song; Jinmai Zhang; Ke Wang; Boyu Chen; Dun Pan; Zhiqiang Li; Changgui Li; Yongyong Shi (BMC, 2018)
Abstract Background Renal hypouricemia (RHUC) is a heterogeneous genetic disorder that is characterized by decreased serum uric acid concentration and increased fractional excretion of uric acid. Previous reports have revealed many functional mutations in two urate transporter genes, SLC22A12 and/or SLC2A9, to be the causative genetic factors of this disorder. However, there are still unresolved patients, suggesting the existence of other causal genes or new mutations. Here, we report an RHUC patient with novel compound heterozygous mutations in the SLC22A12 gene. Case presentation A 27-year-old female presenting with recurrent hypouricemia during routine checkups was referred to our hospital. After obtaining the patient's consent, both the patient and her healthy parents were analyzed using whole-exome sequencing (WES) and Sanger sequencing to discover and validate causal mutations, respectively. The prioritization protocol of WES screened out two mutations of c.269G > A/p.R90H and c.1289_1290insGG/p.M430fsX466, which are both located in the SLC22A12 gene, in the patient. Sanger sequencing further confirmed that the patient's heterozygous c.269G > A/p.R90H mutation, which has been reported previously, derived from her mother, and the heterozygous c.1289_1290insGG/p.M430fsX466 mutation, which was found for the first time, derived from her father. p.R90H, which is highly conserved among different species, may decrease the stability of this domain and was considered to be almost damaging in silicon analysis. p.M430fsX466 lacks the last three transmembrane domains, including the tripeptide motif (S/T)XΦ (X = any amino acid and Φ = hydrophobic residue), at the C-terminal, which interact with scaffolding protein PDZK1 and thus will possibly lead to weak functioning of urate transport through the disruption of the "transporter complex" that is formed by URAT1 and PDZK1. Conclusions We report a Chinese patient with RHUC, which was caused by compound heterozygous mutations of the SLC22A12 gene, using WES and Sanger sequencing for the first time. Mutation-induced structural instability or malfunction of the urate transporter complex may be the main mechanisms for this hereditary disorder.